7h-7=17+4h

Simple and best practice solution for 7h-7=17+4h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7h-7=17+4h equation:


Simplifying
7h + -7 = 17 + 4h

Reorder the terms:
-7 + 7h = 17 + 4h

Solving
-7 + 7h = 17 + 4h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-4h' to each side of the equation.
-7 + 7h + -4h = 17 + 4h + -4h

Combine like terms: 7h + -4h = 3h
-7 + 3h = 17 + 4h + -4h

Combine like terms: 4h + -4h = 0
-7 + 3h = 17 + 0
-7 + 3h = 17

Add '7' to each side of the equation.
-7 + 7 + 3h = 17 + 7

Combine like terms: -7 + 7 = 0
0 + 3h = 17 + 7
3h = 17 + 7

Combine like terms: 17 + 7 = 24
3h = 24

Divide each side by '3'.
h = 8

Simplifying
h = 8

See similar equations:

| y=x^2-7x+6 | | -2x+4=3(x-7) | | 21+9y-10=-277 | | 7x+9=8x+4 | | -7(x+9)=8x+42 | | 3(b+2)+2(x-5)=2 | | (2-z)(5z+3)=0 | | 5m+3=6m+7 | | 3(x+8)-8x=29 | | 3x^2=-6x-2 | | 9p+8q=100 | | 36x-4x+9+25x+7= | | (3x^2-6)=0 | | -(6(5xy+y^3)+5(9xy+7y^3))= | | -2a-11=7+7a | | 5x+5=-21-7x | | -3x^2-4x-5=0 | | 12p+6q=114 | | 2x*2x*2x+3x*3x*3x= | | 6a+2b=20 | | 160x-.8x^2=0 | | 200.00m+(-5600.00)=-2800.00 | | -5(x+5)=-15 | | 6p+4q=56 | | 3+2x=2(2+2x) | | 6x+-9=33 | | 200.00m+(-5600.00)=0.00 | | 3x-2(x+4)=15 | | -1.25+0.15m=0 | | (4,-4)=-5/8 | | (11w+13)+(4w-28)=180 | | 3x+7t=5 |

Equations solver categories